Behavioural insights to support increased consumption of quality protein maize by young children: a cluster randomised trial in Ethiopia. Issue 12 (18th December 2020) - Donato, Katherine; McConnell, Margaret; Han, Dan; Gunaratna, Nilupa S; Tessema, Masresha; De Groote, Hugo; Cohen, Jessica
Abstract : Introduction: Biofortified crops have tremendous potential to improve child nutrition. We tested whether complementing the distribution of quality protein maize (QPM) with a package of interventions informed by behavioural insights could support greater consumption of QPM by young children and translate into improved growth. Methods: We conducted a cluster-randomised trial in Oromia, Ethiopia. Clusters of households with a child between 6 and 35 months were randomised into an arm receiving QPM seed only (320 households, 203 clusters) or an arm receiving QPM seed and a child consumption targeting intervention (290 households, 183 clusters). The intervention package included tools to help caregivers keep QPM separate from conventional maize and to earmark QPM specifically for child consumption, as well as encouragement regarding cooking QPM specifically for young children. We analysed the impact of the intervention on food storage, cooking and consumption behaviours and on anthropometric measures (weight-for-age, height-for-age z scores). Results: The consumption targeting intervention increased the probability of child consumption of QPM in the past week by 17.3 percentage points (pp) (95% CI 9.4 pp to 25.1 pp; p<0.01), increased the probability that QPM flour was stored separately from conventional maize by 46.5 pp (95% CI 38.3 pp to 54.7 pp; p<0.01) and increased the probability that caregivers cooked QPM specifically for young children in the past week by 14.4 pp (95% CI 7.9 pp to 20.9 pp; p<0.01). These effects persisted, but were attenuated, 10 months postintervention. No significant effects on anthropometric outcomes were found. Conclusions: Enhancing the distribution of new, biofortified crop varieties with a consumption targeting campaign can change storage, cooking and consumption behaviours. However, these improved behaviours did not translate into increased growth in this setting. Trial registration number: NCT02710760 and AEARCTR0000786.